Minimization time and battery for a straight movement in MANET - Pattama Longani (2018)
© 2012 Newswood Limited. All rights reserved. In this work we propose two problems that related to a theoretical mobility model previously proposed by Greenlaw and Kantabutra and add some definitions to make the model more complete. The first problem is the minimum time maximum coverage (MTMC) problem to minimize time to move a group of sources which covered a terrain to cover another terrain while all sources can still communicate through a movement duration. The second one is the minimum battery maximum coverage (MBMC) problem to minimize battery usage to move sources which covered a terrain to cover another terrain while all sources can still communicate through a movement duration. The best movement patterns in time consuming and battery usage for both problems are shown by techniques of proof. In addition, we focus on maximum starting and ending coveraged terrain in strainght line fashion only.